Puzzle Media as an Instructional Intervention for Early Reading Development: Evidence from Third-Grade Students in Indonesia - Miftanul Jannah; Azizah Azizah; Nuraini Nuraini; Yusdin bin M Gagaramusu; Kasmawati Kasmawati (Journal of Innovation and Research in Primary Education, 2026)
Low early reading proficiency among elementary school students remains a persistent challenge in Indonesian primary education, particularly with respect to oral reading dimensions such as pronunciation, intonation, voice clarity, and fluency. Puzzle media has emerged as a promising interactive instructional tool; however, empirical evidence of its effectiveness among third-grade students — a transitional learner cohort — remains limited. This study employed a quantitative quasi-experimental design with a pretest–posttest control group arrangement. The participants comprised 40 third-grade students at SDN Inpres 1 Lasoani, divided equally into an experimental class (n = 20) and a control class (n = 20) using a saturated sampling technique. Data were collected through a validated early reading performance test (reliability coefficient r = .87) assessing four reading aspects, and analysed using a Paired Sample T-Test following confirmed normality (Shapiro-Wilk) and homogeneity (Levene's) assumptions. The experimental class demonstrated a statistically significant improvement in reading skills, with mean scores increasing from 76.97 (pretest) to 96.22 (posttest), yielding t(37) = −2.155 and p = .038 (< .05). Gains were consistent across all four assessed reading dimensions. The findings confirm that puzzle media effectively improves holistic oral reading competencies in Grade 3 students, extending prior research predominantly focused on Grade 1 and Grade 2 learners. The results are interpretable through dual coding theory and support the integration of puzzle media as a structured reading intervention aligned with the Merdeka Belajar differentiated learning framework.